PENGARUH SELF-ESTEEM DAN KOMUNIKASI INTERPERSONAL TERHADAP EFEKTIVITAS KERJA GURU - Theresia Sulastri; Sumardi .; Yossa Istiadi (JURNAL MANAJEMEN PENDIDIKAN, 2020)
EFFECT OF SELF-ESTEEM AND INTERPERSONAL COMMUNICATION TOWARD TEACHER EFFECTIVENESSTeacher’s work effectiveness is the one of the elements to be performed in order to reach the school goal. According to the initial study, it is showed that the effectiveness of some private junior high school teachers were not as expected, while actually high work effectiveness among teachers might support excellent output quality implementation. This study aimed to describe, analyze and find out that self-esteem and interpersonal communication bring a positive influence on teacher work effectiveness. The research method was quantitative research and survey research method was path analysis approach. This research was conducted on 5 private junior high schools in the District of Gunung Putri, Bogor Regency. Samples were taken randomly proportionally, totaling 109 of the 150 population. Data collection in this study was using questionnaires as instruments. The results showed that: 1) There was a positive and very significant effect of self-esteem on teacher work effectiveness with a correlation coefficient (β y1) of 0.4769; 2) There was a positive and very significant effect of personal communication on teacher work effectiveness with a correlation coefficient (β y2) of 0.5051; 3) There was a positive and very significant influence on self-esteem and personal communication on work effectiveness teacher with a correlation coefficient (β y12) of 0.5704. Based on the results of the study, the teacher's work effectiveness increased as the influence of self-esteem and interpersonal communication.